Sialylation of β1 Integrins Blocks Cell Adhesion to Galectin-3 and Protects Cells against Galectin-3-induced Apoptosis - Zhuo, Ya (American Society for Biochemistry and Molecular Biology, 2008)
In previous studies, we determined that β1 integrins from human colon tumors have elevated levels of α2-6 sialylation, a modification added by β-galactosamide α-2,6-sialyltranferase I (ST6Gal-I). Intriguingly, the β1 integrin is thought to be a ligand for galectin-3 (gal-3), a tumor-associated lectin. The effects of gal-3 are complex; intracellular forms typically protect cells against apoptosis through carbohydrate-independent mechanisms, whereas secreted forms bind to cell surface oligosaccharides and induce apoptosis. In the current study, we tested whether α2-6 sialylation of the β1 integrin modulates binding to extracellular gal-3. Herein we report that SW48 colonocytes lacking α2-6 sialylation exhibit β1 integrin-dependent binding to gal-3-coated tissue culture plates; however, binding is attenuated upon forced expression of ST6Gal-I. Removal of α2-6 sialic acids from ST6Gal-I expressors by neuraminidase treatment restores gal-3 binding. Additionally, using a blot overlay approach, we determined that gal-3 binds directly and preferentially to unsialylated, as compared with α2-6-sialylated, β1 integrins. To understand the physiologic consequences of gal-3 binding, cells were treated with gal-3 and monitored for apoptosis. Galectin-3 was found to induce apoptosis in parental SW48 colonocytes (unsialylated), whereas ST6Gal-I expressors were protected. Importantly, gal-3-induced apoptosis was inhibited by function blocking antibodies against the β1 subunit, suggesting that β1 integrins are critical transducers of gal-3-mediated effects on cell survival. Collectively, our results suggest that the coordinate up-regulation of gal-3 and ST6Gal-I, a feature that is characteristic of colon carcinoma, may confer tumor cells with a selective advantage by providing a mechanism for blockade of the pro-apoptotic effects of secreted gal-3.